Rhetorical Devices In Political Discourse: A Critical Discourse Analysis Of Donald Trump And Volodymyr Zelensky's Dialogue At WSJ News 2025 - Rizal Rafiuddin; Suhartawan Budianto; Rindrah Kartiningsih (Menulis: Jurnal Penelitian Nusantara, 2026)
This study analyzes rhetorical devices used by Donald Trump and Volodymyr Zelensky in their spontaneous verbal exchange published by The Wall Street Journal in 2025. This study aims to identify the types of rhetorical devices used by both political leaders and to explain how these devices function as instruments of power negotiation in high-stakes political communication. This research applies Norman Fairclough's Critical Discourse Analysis framework, focusing on textual and sociocultural practice dimensions to examine how language constructs power relations and social meaning. This paper used a descriptive qualitative method. The results show that Trump predominantly uses repetition, metaphor, hyperbole, and sarcasm to assert dominance and construct authority. At the same time, Zelensky employs rhetorical questions, rejection of imposed metaphors, emotional appeals, and ethical positioning to resist dominant framing and maintain credibility. Overall, the findings indicate that rhetorical devices play an important role not only as stylistic choices but also as strategic mechanisms for negotiating power and shaping social meaning in spontaneous international political discourse.